Antiapoptotic Agent Sphingosine-1-Phosphate Protects Vitrified Murine Ovarian Grafts. (February 2014) - Tsai, Yung-Chieh; Tzeng, Chii-Ruey; Wang, Chia-Woei; Hsu, Ming-I; Tan, Shun-Jen; Chen, Chi-Huang
Significant follicle loss from frozen ovarian grafts is unavoidable. The authors evaluated the protective effects of the antiapoptotic agent sphingosine-1-phosphate (S1P) on vitrified ovarian grafts. Three-week-old sexually immature female FVB mice were divided into 4 groups, fresh, control without S1P, 0.5 mmol/L S1P, and 2 mmol/L S1P. The ovaries were pretreated with S1P for 1 hour and then cryopreserved by modified vitrification. The frozen–thawed ovaries were autotransplanted under the back muscles of mice for 10 days. Expression of apoptosis-related genes encoding caspase 3 and c-Myc was analyzed in the vitrified ovaries and 10 days after transplantation using real-time quantitative polymerase chain reaction. To quantify the ovarian reserve, anti-Müllerian hormone (AMH) levels and follicles were measured in the 10-day vitrified ovarian grafts. Caspase 3 and c-Myc messenger RNA did not differ significantly in the 4 groups after vitrification but was significantly upregulated in the control group after transplantation. The AMH levels and primordial follicle pool were significantly higher in the S1P-treated groups than in the control group but lower than that in the fresh group. The S1P protects vitrified ovarian grafts from ischemic reperfusion injury rather than from vitrification-associated process.